Characterization of multiscale interactions between high intensity focused ultrasound (HIFU) and tooth dentin: the effect on matrix-metalloproteinases, bacterial biofilms and biological properties. (30th June 2021) - Daood, Umer; Aati, Sultan; Akram, Zohaib; Yee, Joyce; Yong, Celine; Parolia, Abhishek; Lin Seow, Liang; Fawzy, Amr S
Abstract : Characterization of multiscale interactions between high intensity focused ultrasound (HIFU) and dentin collagen and associated matrix-metalloproteinases, in addition to the analysis of the effect of HIFU on bacterial biofilms and biological properties. Abstract : The aim of this study was to characterize multiscale interactions between high intensity focused ultrasound (HIFU) and dentin collagen and associated matrix-metalloproteinases, in addition to the analysis of the effect of HIFU on bacterial biofilms and biological properties. Dentin specimens were subjected to 5, 10 or 20 s HIFU. XPS spectra were acquired and TEM was performed on dentin slabs. Collagen orientation was performed using Raman spectroscopy. Calcium measurements in human dental pulpal cells (hDPCs) were carried out after 7 and 14 days. For macrophages, CD36+ and CD163+ were analysed. Biofilms were analyzed using CLSM. Tandem mass spectroscopy was performed for the detection of hydroxyproline sequences along with human MMP-2 quantification. Phosphorus, calcium, and nitrogen were detected in HIFU specimens. TEM images demonstrated the collagen network appearing to be fused together in the HIFU 10 and 20 s specimens. The band associated with 960 cm −1 corresponds to the stretching ν 1 PO4 3− . The control specimens showed intensive calcium staining followed by HIFU 20 s > HIFU 10 s > HIFU 5 s specimens. Macrophages in the HIFU specimens co-expressed CD80+ and CD163+ cells. CLSM images showed the HIFU treatment inhibiting bacterial growth. SiteScore propensity determined the effect of HIFU on the binding site with a higher DScore representing better site exposure on MMPs. Multiscale mapping of dentin collagen after HIFU treatment showed no deleterious alterations on the organic structure of dentin.